Esomeprazole tidak meningkatkan efek antibakteri natrium hipoklorit : Kajian in vitro pada Enterococcus faecalis dan Escherichia coli (Laporan Penelitian) - Aurellia Nadia Cendana; Didi Nugroho (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Proton pump inhibitors are drugs used to treat gastric acid secretion disorders by selectively and irreversibly inhibiting the proton pump. Previous study has shown that the addition of proton pump inhibitors to sodium hypochloride has a higher antibacterial effect. This research was conducted on Enterococcus faecalis and Escherichia coli which have proton pumps. Objective: To examine the antibacterial effect of the combination of NaOCl 5,25% with esomeprazole on the growth of E. faecalis and E. coli. Methods: This is an in vitro study with a post-test only control design. This study was done at the MiCORE Laboratory of Trisakti University Faculty of Dentistry. There were six treatments for E. faecalis and E. coli. The six treatment groups were esomeprazole 4%, esomeprazole 8.5%, omeprazole 8.5% combined with NaOCl 5.25%, esomeprazole 8.5%, NaOCl 5.25%, and aquadest. Results: In the treatment of esomeprazole 8.5%, combination of NaOCl 5.25% with omeprazole 8.5%, and aquadest shown that no inhibition zones were found in both bacteria. The average value of the inhibition zone against E. faecalis was as follows, esomeprazole 4% combination (16.18 mm (SD±1,60)), esomeprazole 8,5% combination (14.20 mm (SD±0,21)), and NaOCl 5,25% (25.90 mm (SD±1,46)). Against E. coli, the average inhibition zone values were obtained as follows, esomeprazole 4% combination (16.68 mm (SD±1,68)), esomeprazole 8,5% combination (13.87 mm (SD±0,07)), and NaOCl 5.25% (30.22 mm (SD±1,08)). Conclusion: The combination of sodium hypochloride with esomeprazole was not better than 5,25% sodium hypochloride in inhibiting bacterial growth of E. faecalis and E. coli.